2020
DOI: 10.1021/acs.joc.9b03203
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Strong Ligand Sensitivity in Pd-Catalyzed α-Arylation of Enolates from Ketones, Esters, and Nitroalkanes

Abstract: The mechanism of the Pd-catalyzed α-arylation of three model enolates is studied focusing on an analysis of their very different reactivities. In particular, the low reactivity of nitronates under standard arylation conditions and their high sensitivity to the nature of catalytic systems are addressed. The three canonical steps for each of the reaction systems are examined, and key trends surrounding the stability of intermediates and transition states are delineated. A framework based on molecular orbital ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Nevertheless, a recent theoretical study on palladium-catalyzed α-arylation of ketones with phosphine ligands suggested that reductive elimination is the rate-limiting step. 21 As expected, the nature of the allyl derivative ligand has no meaningful influence on the enantioselectivity (72% ee, entry 2 vs. 77% ee, entry 6) (95% ee, entries 3 and 4 vs. 92% ee, entry 7 vs. 92%, entry 8) since the generated catalytic species is the same. As isolated yields are good to excellent, the effect of the nature of the allyl derivative ligand on catalytic activity cannot be confidently addressed.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, a recent theoretical study on palladium-catalyzed α-arylation of ketones with phosphine ligands suggested that reductive elimination is the rate-limiting step. 21 As expected, the nature of the allyl derivative ligand has no meaningful influence on the enantioselectivity (72% ee, entry 2 vs. 77% ee, entry 6) (95% ee, entries 3 and 4 vs. 92% ee, entry 7 vs. 92%, entry 8) since the generated catalytic species is the same. As isolated yields are good to excellent, the effect of the nature of the allyl derivative ligand on catalytic activity cannot be confidently addressed.…”
Section: Resultssupporting
confidence: 55%
“…Nevertheless, a recent theoretical study on palladium-catalyzed α-arylation of ketones with phosphine ligands suggested that reductive elimination is the ratelimiting step. 21 As expected, the nature of the allyl derivative ligand has no meaningful influence on the enantioselectivity (72% ee, entry 2 vs. 77% ee, entry 6) (95% ee, entries 3 and 4…”
Section: Paper Dalton Transactionssupporting
confidence: 55%
“…Since a nitro group has stronger electron-withdrawing property, the pKa values of nitroalkanes are approximately 8.6-10.2, [31] which are similar to those for activated 1,3dicarbonyl compounds (pKa 9-13). [25] Based on this analysis, we decided to explore the possibility to apply nitroalkanes as suitable nucleophiles, [32] and subsequently revealed that their coupling with (hetero)aryl halides worked well by using our newly developed Cu/oxalamide catalytic system. [33] This result represents the first copper-catalyzed α-arylation/ alkenylation of nitroalkanes with (hetero)aryl halides and vinyl halides.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous α-arylation reagents have been developed, their applications are limited because they involve different strategies and transmetalation . Furthermore, major efforts toward the α-arylation of aliphatic enolates and cyclic carbonyl compounds have scantly been reported . It reveals that some shortcomings still exist in the direct α-arylation of cyclic carbonyl compounds.…”
mentioning
confidence: 99%